A hybrid method for evaluation of maintainability towards a design process using virtual reality. (February 2020) - Guo, Ziyue; Zhou, Dong; Zhou, Qidi; Mei, Shunfeng; Zeng, Shengkui; Yu, Dequan; Chen, Jiayu
Highlights: A life case of applying virtual reality to the design and manufacturing process. We established a complete maintainability design process that integrates virtual reality. A quantitative analysis of how virtual reality can help designers make decisions. Virtual reality can improve the designer's understanding of the product. The proposed method achieved good feasibility and effect for the maintainability design. Abstract: Modern society has a high demand for manufactured products in almost all fields. To achieve high availability and reduce costs, products require good maintainability, which is an intrinsic property that is decided mostly in the design and manufacturing stages. Design evaluation plays an important role in improving the maintainability of products. At present, though designers can verify maintainability by conducting virtual maintenance simulations on digital mockups (DMUs) to test design and manufacturing effects, this approach requires substantial time and specialist knowledge. In this paper, a hybrid maintainability evaluation method based on virtual reality (VR) and fuzzy comprehensive evaluation (FCE) is proposed to solve the problem. First, an evaluation index system is established to launch the design requirements. A VR-based method is proposed to help conduct the immersive maintenance simulation in a virtual environment. A maintenance simulation monitoring platform is developed to help designers evaluate maintainability and make decisions. Finally, FCE is leveraged to give a comprehensive evaluation result for maintainability status. A case of comparative experiments was conducted to verify the effectiveness of the proposed method. The participants of two groups were encouraged to evaluate the maintainability of a fluid physical experiment rack for a space station based on a traditional method and the proposed method. After the physical verification and result analysis, the proposed method was demonstrated to have better abilities to help predict design flaw and make design decision.